Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products and Services: Phase 1: Pacific: Country Report: Marshall Islands - Hart, Kevin; Vander Velde, Nancy (Technical Centre for Agricultural and Rural Cooperation, 2005)
The report presents a general overview of the Marshall Islands with emphasis on the current status of agriculture, fisheries, and communications. Environmental and socio-economic conditions that restrict agricultural potential are described...